PENGARUH KONSELING REALITA TERHADAP PEMBENTUKAN KEMANDIRIAN PADA SISWA SMPN 2 KURIPAN - Elis Sulistiya; Jumailiyah Jumailiyah (Jurnal Paedagogy, 2016)
The purpose of this study was to determine the effect of Reality Counseling on the Establishment of Independence in Students at SMPN 2 Kuripan. The type of experiment used in this research is Pre-experimental Design (non-design) or impure experiment, and one form of the experiment is the One-Group Pretest-Posttest Design. The population in this study were all students of SMPN 2 Kuripan who experienced problems in independence , the sample used was 10 students. In this study, the data collection method used was a questionnaire method as the main method. To analyze data using the t-test formula. The results of the study were: the t value of 4.756 and the t table value at the 5% significance level with N = 10 of 2.262. Thus the t value is greater than the t value in the table (4.756> 2.262) so that it can be concluded "significant". This shows that the null hypothesis () is rejected and the alternative hypothesis (Ha) is accepted. So the conclusion of the analysis in this study is that there is an effect of reality counseling on the formation of independence in students at SMPN 2 Kuripan.